PLOTTING A DIAGRAM OF NATURAL GAS INTERCHANGEABILITY FOR THE ENERGY MARKET OF GEORGIA (World Science, 2020)
The increase in the cost of energy and the appearance of gases of various qualities led to the fact that calculations in the gas industry began to be made by measuring thermal energy.  To this day, in Georgia, the calculation of the amount of natural gas when paying for the used gas is in cubic meters.  As for the study of processes and parameters in the Georgian gas sector, it turned out that these processes are clearly stochastic.  Therefore, the purpose of the work is to develop criteria for the interchangeability of natural gas, in particular, a diagram of the interaction between the Wobbe index in total proportions of propane and nitrogen equivalent for the Georgian gas market, based on stochastic processes.  Thus, for the first time, an original methodology for plotting the Wobbe Index (calorific value) of interchangeable natural gases supplied to Georgia was developed.